HAMBATAN DAN STRATEGI KOMUNIKASI ANTARBUDAYA MAHASISWA ETNIK KALIMANTAN DAN MAHASISWA ETNIK JAWA DI UNIVERSITAS SAHID SURAKARTA - Sayekti, Amalia; Wisudawanto, Rahmat; ., MUSTA'AN (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2019)
Background: Communication that occured between two or more people of different cultures is a manifestation of intercultural communication in daily life. The differences culture can make barriers in communication. Thus, Intercultural communication strategy is needed to suppress the possibility of intercultural communication barriers.Objective: The aims of this study is to classify and describe the intercultural communication barriers and to explain intercultural strategies in overcoming communication barriers from Kalimantan and Java ethnic students of 2016/2017 in University of Sahid Surakatra.Methods: This research used descriptive qualitative method. The data were used in this study was the result of observation and in-depth interviews gradually to Kalimantan and Java ethnic students of 2016/2017 in University of Sahid Surakatra.Result: The results of this study indicate that barriers to intercultural communication occured in Kalimantan and Java ethnic students of 2016/2017 at University of Sahid Surakatra are (1) the tendency to judge negative, (2) anxiety or high tension, (3) language differences (4) non-verbal misunderstanding (5) preconceptions and stereotypes and (6) assuming similarity. The Implementation of intercultural communication strategies in overcoming these barriers are (1) persuasive communication can be used when the barriers of language differences, the tendency to judge negative, anxiety or high tension, and non- verbal misunderstanding. (2) informative communication can be used to the barriers of preconceptions and stereotypes and assuming similarity. (3) coercive communication sometimes uses for communication barriers of language differences.